Mapping the Future: Prioritizing Selection Factors for Tomorrow's Professions - Ayyildiz, Ertugrul; Erdogan, Melike; Kesici, Busra; Aydin, Nezir (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Career selection significantly impacts an individual's financial stability, job satisfaction, and overall quality of life. As industries evolve with technological advancements and digital transformation, understanding the key factors influencing career choices has become increasingly important. This study aims to prioritize the factors affecting future career decisions using a structured multi-criteria decision-making approach. A framework comprising six main criteria and 24 sub-criteria was developed through expert opinions and a literature review. The Spherical Fuzzy Step-wise Weight Assessment Ratio Analysis (SF-SWARA) is applied to assess and rank these factors while accounting for uncertainty. The results indicate that Starting Salary is the most influential factor, followed by Alignment with Personal Goals, emphasizing the role of financial security and personal motivation in career decisions. Conversely, Remote Work Potential was ranked as the least important factor, suggesting that direct workplace interaction and industry-specific requirements remain crucial.
Keywords: Career selection; Future profession; spherical fuzzy numbers; SWARA; Computer Science